BONDING AND ATTACHMENT EXPERIENCE AMONG POSTNATAL MOTHERS WITH SPONTANEOUS CHILDBIRTH - Fauziah H Wada; Yayi Suryo Prabandari; Elsi Dwi Hapsari (Belitung Raya Foundation, Indonesia, 2020)
Background: Bonding is an emotional bond between a mother and a baby that develops gradually and immediately after birth until it is formed into an attachment. Bonding is considered important to ensure the baby’s protection. However, bonding remains challenging for mothers with spontaneous childbirth because they are most likely to focus on themselves. Objective: To explore the bonding and attachment experience among postpartum mothers with spontaneous childbirth. Methods: This was a qualitative study with a phenomenological approach. Data were collected from nine participants using semi-structured interviews and observations. Data were analyzed using Colaizzi’s analysis method. Results: Five themes emerged, namely 1) feeling relieved and happy with the birth of the baby, 2) bonding and attachments are important, 3) stimulating the baby’s sense, 4) the need of social supports in bonding and attachment, and 5) internal and external factors of bonding and attachment. Conclusion: Bonding and attachment are very important that should be done by the mothers to the baby. However, it takes time and needs the supports from the husbands, parents, relatives, and health workers. Therefore, nurses or midwives should pay attention to this process to create the better bonding and attachment between the mothers and the babies.